2016
DOI: 10.1093/cercor/bhw128
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Network Topology in Patients with Stable and Progressive Mild Cognitive Impairment and Alzheimer's Disease

Abstract: Recent findings suggest that Alzheimer's disease (AD) is a disconnection syndrome characterized by abnormalities in large-scale networks. However, the alterations that occur in network topology during the prodromal stages of AD, particularly in patients with stable mild cognitive impairment (MCI) and those that show a slow or faster progression to dementia, are still poorly understood. In this study, we used graph theory to assess the organization of structural MRI networks in stable MCI (sMCI) subjects, late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
110
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(133 citation statements)
references
References 88 publications
23
110
0
Order By: Relevance
“…Our results are consistent with an MRI study performed by Pereira et al (30) that found in two large, multicenter cohorts a progressive degradation in the connectivity of brain functional networks in patient groups having the same characteristics as in our study, including MCI converters followed up for 1 and 3 y. The most striking similarity with our study was the finding of a progressive increase in modularity with severity of the disease, suggesting a degradation of whole-brain networks into segregated components.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with an MRI study performed by Pereira et al (30) that found in two large, multicenter cohorts a progressive degradation in the connectivity of brain functional networks in patient groups having the same characteristics as in our study, including MCI converters followed up for 1 and 3 y. The most striking similarity with our study was the finding of a progressive increase in modularity with severity of the disease, suggesting a degradation of whole-brain networks into segregated components.…”
Section: Discussionsupporting
confidence: 93%
“…In the dementia stages of AD grey matter networks seem to show a more random topology, as indicated by a reduced normalized clustering (i.e., gamma) and/or normalized path length (i.e., lambda) (He, Chen, & Evans, 2008;Pereira et al, 2016;Tijms et al, 2013a;Yao et al, 2010). In the present study we investigated whether a more random grey matter network organization is associated with early cognitive changes in individuals with SCD.…”
Section: Discussionmentioning
confidence: 92%
“…Although, the biological meaning of structural similarities is not yet fully understood, grey matter similarity has been demonstrated to be associated with synchronized maturation between brain regions (Alexander‐Bloch and Bullmore, ; Alexander‐Bloch, Raznahan, Bullmore, & Giedd, b; Andrews, Halpern, & Purves, ), which might be reflected by a higher degree of clustering. Previous cross‐sectional studies have demonstrated that alterations of grey matter network parameters are associated with disease severity (Pereira et al, ; Tijms et al, ; Yao et al, ; Zhou and Lui, ) and with the degree of cognitive impairment in AD (Tijms et al, ). A group‐based network study suggested that grey matter networks that more resemble randomly organized networks are associated with future progression to dementia in individuals with mild cognitive impairment (Pereira et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they found decreased small-world index in AD. Pereira et al [97] constructed structural brain networks of stable MCI (sMCI) patients, late MCI converters (lMCIc), early MCI converters (eMCIc), and AD patients to investigate topology structure across groups. They found that, compared with the HC group, all patient groups exhibited increased path length, reduced transitivity, and increased modularity, and the patient group showed decreased smallworld index.…”
Section: Structural Brain Network In Admentioning
confidence: 99%